The Approach of the World’s Dominant Religions Toward the Taking of Life and Suicide - Chałubińska, Zuzanna (Pedagogika Społeczna Nova, 2025)
The phenomenon of suicide has been causing a heated debate in the minds of people for centuries. The mysterious phenomenon was described from antiquity as an act of freedom worship, to the Middle Ages as a grave sin against God. Consideration of the attitudes we take toward the act of suicide is still a debatable issue today. Judaism, Islam and Christianity are all religions that oppose taking a life. An important question should be asked here: what is in the background of the contempt for committing suicide? When analysing the literature and articles on religious attitudes toward the phenomenon of suicide, we can find many aspects related to exclusion and ostracism in historical perspective. In contrast to the attitude towards suicide, chosen religions relate differently to the death of people, who had their lives taken as a consequence of war or in the name of religion. Using the example of Janusz Korczak, who sacrificed his life for the children during World War II, we can find publications and words of praise towards his martyrdom. For it was not the fault of Korczak and millions of other people, during this and other wars waged around the world for centuries, that they died. People, who died in the name of politics, nationality disputes or just religions. So, if we focus from this perspective on suicide deaths and the reasons for individuals’ decisions to take their own lives, we can find fault with social stereotypes and the stigmatization of social groups that are at risk of suicide crisis. Thus, a fundamental question must be asked here: does religion rightly place the suffering of victims of international conflicts above that of people in suicidal crisis, who not rarely take their own lives because of society’s approach? The stance of the various religions, which clearly express negative approach towards the intentional taking of life differs in terms of attitude about death itself and death martyred or taken in the name of religion. In this article, I shall analyse the catechisms and dogmas of chosen religions related to the above issues and compare their stances towards various causes of human death.